PEMBERDAYAAN DESA BLIMBINGSARI SEBAGAI DESA WISATA TAHUN KEDUA - Ni Putu Meri Dewi Pendit; Putu Ayu Anggya Agustina (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
The tourism potential in Jembrana Regency, Bali, requires further development to enrich tourists' choice of attractions. Blimbingsari Village, Melaya District, has great potential to be developed as a higher-level tourist village. In 2024, the Village Service Development program focuses on strategic training, including introducing local culture in English, quality of service training, coffee-making training with grant tools, and installing tourism identity icons. This program is a continuation of similar activities carried out in 2023. English training was given to 23 village youth to improve communication skills and to be able to tell about local culture to tourists while fostering pride in local cultural values. In addition, training in operating coffee equipment and serving menus such as espresso, long black, and caffè latte is designed to empower local business actors. This program improves community skills and opens opportunities for additional income and new businesses, especially in the coffee sector. The results of the activities show a positive impact, both in increasing human resource capacity and village tourism attractions. Tourists can now enjoy authentic cultural and culinary experiences, strengthening Blimbingsari Village's position as a high-value tourist destination.